Season of prescribed fire determines grassland restoration outcomes after fire exclusion and overgrazing. Issue 9 (5th September 2021) - Novak, Erin N.; Bertelsen, Michelle; Davis, Dick; Grobert, Devin M.; Lyons, Kelly G.; Martina, Jason P.; McCaw, W. Matt; O'Toole, Matthew; Veldman, Joseph W.
Abstract: Fire exclusion and mismanaged grazing are globally important drivers of environmental change in mesic C4 grasslands and savannas. Although interest is growing in prescribed fire for grassland restoration, we have little long‐term experimental evidence of the influence of burn season on the recovery of herbaceous plant communities, encroachment by trees and shrubs, and invasion by exotic grasses. We conducted a prescribed fire experiment (seven burns between 2001 and 2019) in historically fire‐excluded and overgrazed grasslands of central Texas. Sites were assigned to one of four experimental treatments: summer burns (warm season, lightning season), fall burns (early cool season), winter burns (late cool season), or unburned (fire exclusion). To assess restoration outcomes of the experiment, in 2019, we identified old‐growth grasslands to serve as reference sites. Herbaceous‐layer plant communities in all experimental sites were compositionally and functionally distinct from old‐growth grasslands, with little recovery of perennial C4 grasses and long‐lived forbs. Unburned sites were characterized by several species of tree, shrub, and vine; summer sites were characterized by certain C3 grasses and forbs; and fall and winter sites were intermediate in composition to the unburned and summer sites. Despite compositional differences, all treatments had comparable plot‐level plant species richness (range 89–95 species/1000 m 2 ). At the local‐scale, summer sites (23 species/m 2 ) and old‐growth grasslands (20 species/m 2 ) supported greater richness than unburned sites (15 species/m 2 ), but did not differ significantly from fall or winter sites. Among fire treatments, summer and winter burns most consistently produced the vegetation structure of old‐growth grasslands (e.g., mean woody canopy cover of 9%). But whereas winter burns promoted the invasive grass Bothriochloa ischaemum by maintaining areas with low canopy cover, summer burns simultaneously limited woody encroachment and controlled B. ischaemum invasion. Our results support a growing body of literature that shows that prescribed fire alone, without the introduction of plant propagules, cannot necessarily restore old‐growth grassland community composition. Nonetheless, this long‐term experiment demonstrates that prescribed burns implemented in the summer can benefit restoration by preventing woody encroachment while also controlling an invasive grass. We suggest that fire season deserves greater attention in grassland restoration planning and ecological research.